2016
DOI: 10.1016/j.jmbbm.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dimethyl sulfoxide used as a solvent on the physical properties and long-term dentin bonding of hydrophilic resins

Abstract: The use of DMSO as a new solvent in adhesive dentistry improves dentin bonding of relatively hydrophilic resins over time. 2% DMSO incorporation in BisGMA/HEMA resins should be sufficient to reduce bond strength loss without compromising polymer mechanical strength and physical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
2
20
0
1
Order By: Relevance
“…It also possesses the polarity needed to break down water's self-association and forms stable complexes with water to create "hydrophobic water" [183,184]. Recent studies have shown increase both in immediate and long-term bond strength [185,181,[186][187][188]. The increase in immediate bod strength may be due to DMSOinduced improvement in dentin wettability [189], which may be the reason for the better adhesive penetration [181].…”
Section: Removal Of the Unbound/residual Water Within The Hlmentioning
confidence: 99%
“…It also possesses the polarity needed to break down water's self-association and forms stable complexes with water to create "hydrophobic water" [183,184]. Recent studies have shown increase both in immediate and long-term bond strength [185,181,[186][187][188]. The increase in immediate bod strength may be due to DMSOinduced improvement in dentin wettability [189], which may be the reason for the better adhesive penetration [181].…”
Section: Removal Of the Unbound/residual Water Within The Hlmentioning
confidence: 99%
“…The transport of oral fluids (saliva, organic acids produced by the oral biofilm and water) through the adhesive polymer structure is crucial to the degradation of the tooth-adhesive interfaces [ 3 , 38 , 39 ], and this has been related to the impairment of some physical properties of the adhesive systems [ 40 ]. Thus, the evaluation of water sorption and solubility is crucial to analyze the performance of innovative-bioactive adhesive systems [ 17 , 41 ]. In the current study, the experimental adhesive system with 2 wt.% of ZnCl 2 did not suffer higher water sorption and solubility than the model blend Zn0 (control).…”
Section: Discussionmentioning
confidence: 99%
“…Although DMSO was originally proposed as a potential solvent to simplify the reaction of polymerization in adhesive applications [16], only recently several in vitro studies have shown that DMSO pretreatment of dentin can improve the immediate and long-term dentin bond strength and lower long term nanoleakeage from relatively low (0004%) to high concentrations (50%) [17][18][19][20][21][22][23][24]. Enhanced monomer penetration into the collagen matrix [18,21] has been suggested as a possible mechanism but no systematic information is available regarding the effect of DMSO on adhesive monomer penetration.…”
Section: Introductionmentioning
confidence: 99%